Development of an LMS-Based Microcredential Course for Teachers to Detect and Report Bullying: Training Effectiveness Evaluation - Devita Wiwik Widyasari; Ayu Lestari Hasan; Adriansyah Hermawan Juasrib; Arianti Mallimbu; Asti Magfirah; Miraekel Lebang Malik (Jurusan Teknik Informatika dan Komputer, 2024)
This study aimed to evaluate the effectiveness of a microcredential course delivered via a Learning Management System (LMS) for teachers to improve their ability to detect and report bullying incidents. Despite the increasing prevalence of bullying in schools, teacher preparedness and practical skills for intervention remain limited. This study addresses this gap by providing evidence-based professional development that integrates knowledge, self-efficacy, and practical competency. A quasi-experimental design was employed, involving 120 teachers randomly assigned to intervention (n = 60) and control groups (n = 60). The intervention group completed an LMS-based microcredential course featuring modular content, scenario-based simulations, and formative assessments. Data collection included pre- and post-intervention tests, self-efficacy surveys, and practical scenario evaluations. Statistical analyses comprised paired and independent t-tests, effect size calculations, and correlation analyses for engagement metrics. Teachers in the intervention group demonstrated significant improvements in knowledge (pretest 56.4 ± 7.8 → posttest 83.6 ± 6.5), self-efficacy (3.1 ± 0.6 → 4.5 ± 0.4), and practical competencies (48.5 ± 5.2 → 85.1 ± 4.8), whereas the control group showed no significant change. Engagement metrics positively correlated with outcome measures (r = 0.62, p < 0.001), highlighting the importance of interactive learning elements. The findings suggest that LMS-based microcredential courses can effectively enhance teacher competencies in bullying detection and reporting, providing a scalable and standardized professional development model. Limitations include the urban-only sample, short-term evaluation, and reliance on simulations rather than real-world observation. This study contributes empirical evidence on teacher-focused digital professional development, emphasizing microcredentialing and scenario-based learning. Future research may explore longitudinal retention, multi-site replication, and blended approaches combining online and in-person training.